Comparing two different superovulation protocols on ovarian activity and fecal glucocorticoid levels in the brown brocket deer (Mazama gouazoubira) - Zanetti, Eveline S. [UNESP]; Munerato, Marina S. [UNESP]; Cursino, Marina S. [UNESP]; Duarte, Jose Mauricio B. [UNESP] (Biomed Central Ltd., 2014)
Background: Stress is a limiting factor in assisted reproduction in wild animals maintained in captivity. However, the knowledge of assisted reproduction techniques for wild animals is useful for future in situ and ex situ conservation programs. Thus, this study evaluated the ovulation rate, presence of functional corpora lutea and fecal glucocorticoid levels following treatments promoting superovulation in captive brown brocket deer.Methods: The crossover design used six hinds, allocated to two groups (n = 6): eCG Treatment, CIDR for 8 days, followed by 0.25 mg of EB on day 0, 700 IU of eCG on day 4 following device insertion and 265 mug of PGF2alfa on day 8; and FSH Treatment, CIDR for 7.5 days, followed by 0.25 mg of EB on day 0, 130 mg of FSH in 8 equal doses and 265 mug of PGF2alfa on day 7.5. Induced adrenal activity and treatment efficacy were evaluated by corpora lutea (CL) counts and fecal glucocorticoid and progestin concentration (ng/g feces) analyses for five different phases: Pre, two days before treatment; Early, first four days of treatment; Late, last four days of treatment; Total, entire treatment period; and Post, five days posttreatment.Results: eCG Treatment resulted in the highest number of CL (P lower than 0.05). There was no significant difference for fecal glucocorticoid concentrations in five different time periods between the treatments; however Pre fecal glucocorticoid concentrations (90.06+/-19.64) were significantly different from Late (200.76+/-26.39) within FSH Treatment. The mean fecal progestin concentration and mean ovulation rate were higher in eCG Treatment (4293.69+/-769.47, 7.0+/-1.8) than in FSH Treatment (1571.26+/-240.28, 2.6+/-0.8) (P lower than or equal to 0.05).Conclusions: Although the eCG Treatment induced a good superovulatory response, with the formation of functional corpora lutea, we cannot yet affirm that we have established a suitable protocol for induction of SOV in the species M. gouazoubira because approximately 65% of the deer showed premature regression of the corpora lutea. Moreover, multiple FSH applications in FSH Treatment resulted in a low ovulation rate and induced an increase in fecal glucocorticoid levels.
Keywords: Reproduction biotechniques; Neotropical deer; Fecal glucocorticoids; Fecal progestin